2021
DOI: 10.3847/1538-4357/ac0e9f
|View full text |Cite
|
Sign up to set email alerts
|

Thresholds for Particle Clumping by the Streaming Instability

Abstract: The streaming instability (SI) is a mechanism to aerodynamically concentrate solids in protoplanetary disks and trigger the formation of planetesimals. The SI produces strong particle clumping if the ratio of solid to gas surface density—an effective metallicity—exceeds a critical value. This critical value depends on particle sizes and disk conditions such as radial drift-inducing pressure gradients and levels of turbulence. To quantify these thresholds, we perform a suite of vertically stratified SI simulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
131
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(145 citation statements)
references
References 71 publications
13
131
1
Order By: Relevance
“…These pieces of information could be used as a guide and predict the properties near the mid-plane of a vertically stratified disc, which helps isolate the effects of vertical sedimentation of the gas and the dust particles by comparison. We note that Li & Youdin (2021) recently found no apparent connection between the linear growth of the streaming instability in an unstratified disc and the strong clumping of solids in a vertically stratified one. Therefore, we believe it is even more imperative to further investigate the nonlinear saturation of the streaming instability before understanding its connection to vertically stratified discs.…”
Section: Introductioncontrasting
confidence: 60%
See 3 more Smart Citations
“…These pieces of information could be used as a guide and predict the properties near the mid-plane of a vertically stratified disc, which helps isolate the effects of vertical sedimentation of the gas and the dust particles by comparison. We note that Li & Youdin (2021) recently found no apparent connection between the linear growth of the streaming instability in an unstratified disc and the strong clumping of solids in a vertically stratified one. Therefore, we believe it is even more imperative to further investigate the nonlinear saturation of the streaming instability before understanding its connection to vertically stratified discs.…”
Section: Introductioncontrasting
confidence: 60%
“…For larger particles, the vertical diffusion coefficient shows some variation but generally is confined in between 10 −3 𝑐 s 𝐻 g and 10 −2 𝑐 s 𝐻 g , with the maximum at 𝜏 s 0.3, while the radial diffusion coefficient shows monotonic increase with increasing 𝜏 s until 𝜏 s ∼ 1, where 𝐷 p, 𝑥 ∼ 10 −3 𝑐 s 𝐻 g . We note that in contrary to 𝐷 p,𝑧 > 𝐷 p,𝑥 in our Model B, previous vertically stratified simulations with 𝜏 s,max = 1 showed that 𝐷 p,𝑧 𝐷 p, 𝑥 (Bai & Stone 2010b;Schaffer et al 2018; see also Li & Youdin 2021), and we discuss this further in Section 4.5.…”
Section: Turbulent Diffusionmentioning
confidence: 56%
See 2 more Smart Citations
“…First, the surface density of solids would be boosted near 45 au, including the contribution from the cold finger effect (Drazkowska & Alibert 2017). This could potentially produce, if grains stick and grow to become large enough (Birnstiel et al 2016), favorable conditions for the streaming instability (Carrera et al 2015, Yang et al 2017, Li & Youdin 2021. Second, for temperatures below 30 K, CO can be destroyed on grains (chemistry mediated by cosmic ray ionization), producing CO 2 , CH 3 OH (methanol), and other hydrocarbons (e.g., Bosman et al 2018), all of which have relatively high sublimation temperatures and can remain on a surface.…”
Section: Discussionmentioning
confidence: 99%